Igniting the IT Flame: a Study on IT Skills and Knowledge in Accounting Programs Among Graduating Students in Oman - Shatha Hilal Alshuriqi; Balqees Saed Al Mahrouqi; Mohammed Muneerali Thottoli (Profesional Muda Cendekia Publishing, 2023)
Purpose: Accountants have always been information technology (IT) users, and the case for increasing IT skills and Knowledge by accounting practitioners and graduates is stronger than ever. In business, IT is widely used and is getting more so. Without IT tools, achieving users' requirements for financial statements and other management information systems reports is no longer possible. Academics and practitioners have recognized the significance and IT (skills and Knowledge) in achieving success in the competitive business environment. Accountants who work for businesses, IT (skills and Knowledge) have necessitated the development of a new type of accountant, which is the focus of this study. Hence, this study aims to know the relationship between IT (skills and Knowledge) of accounting graduating students in Oman and university accounting programs. Design/ Methodology/ Approach: The units of analysis for this study are graduating students in Oman. It used a survey for the year 2022 to study the effect of IT (skills and Knowledge) and accounting programs among graduating students in Oman. The present research tested its hypotheses and utilized its variables using the PLS software for data analysis. Findings: The result revealed that IT Knowledge was significant with Accounting Programs where it was p<0.01, t ˃2.33. This result indicates that IT Knowledge has a significant impact on Accounting Programs. Further, the result revealed that IT Skills were also significant in Accounting Programs where it was p< 0.01, t=2.434. This result indicates that IT Skills have a significant impact on Accounting Programs.